1997
DOI: 10.1007/s001340050487
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of acute renal failure and outcome of haemodiafiltration in intensive care

Abstract: General measures of severity are not useful in predicting the outcome of ARF. Only the nature and number of dysfunctioning organ systems and massive transfusion at the beginning of CVVHDF and the age of the patients gave a reliable prognosis in this group of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
2
9

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(58 citation statements)
references
References 30 publications
5
42
2
9
Order By: Relevance
“…Other authors [31] have also demonstrated that the occurrence of postoperative mild to moderate acute kidney injury (AKI) was associated with a mortality rate of 10% to 20%, indings that are consistent with results from our study. Interestingly, AKI incidents in this study were associated with even much higher in-hospital mortality rates (50%) despite the application of postoperative CVVH.…”
Section: Discussionsupporting
confidence: 83%
“…Other authors [31] have also demonstrated that the occurrence of postoperative mild to moderate acute kidney injury (AKI) was associated with a mortality rate of 10% to 20%, indings that are consistent with results from our study. Interestingly, AKI incidents in this study were associated with even much higher in-hospital mortality rates (50%) despite the application of postoperative CVVH.…”
Section: Discussionsupporting
confidence: 83%
“…Other studies have indicated that comorbid conditions or surgical complications only partly account for the mortality difference between patients with and without ARF (23,24). Multiple organ failures primarily contributed to high mortality in patients with ARF and were strong predictors of death (6,26). In our study, when the logistic regression model included other organ failure, ARF was still significant for death, suggesting that ARF is an independent predictor of death.…”
Section: Figure 2 Odds Ratio (Or) For Arf Defined By Diagnosis Codinmentioning
confidence: 47%
“…These results are similar to those of previous research. [23] The mortality of patients who received conservative treatment was 35.6%, while that of patients who received RRT was 23.2%. Thus, early initiation of dialysis seems important for patients with severe ARF, especially the elderly.…”
Section: Discussionmentioning
confidence: 95%